INTEGRATED QUALITY MANAGEMENT IN EDUCATION: A CASE STUDY IN A SECONDARY SCHOOL - Al-Amin; Farida Asy'ari (International Journal of Teaching and Learning, 2026)
This research examines the implementation of Total Quality Management (TQM) in Secondary Schools as an effort to improve the quality of education. The purpose of this study is to understand how TQM strategies are applied in the educational context and identify their impact on various aspects of school operations. The research method used was literature review. The results show that the implementation of TQM in secondary schools creates a consistent and systematic mechanism in planning, implementing and evaluating the education process. It also increases the participation and involvement of all stakeholders and strengthens collaboration between teachers, students, parents and other school staff. In addition, TQM promotes a culture of continuous improvement and operational efficiency, which overall contributes to improved education quality and student learning satisfaction. The conclusion of this study confirms that TQM is an effective approach in improving the quality of education in secondary schools. With TQM in place, schools can achieve higher quality standards, create a more conducive learning environment and meet students' needs more effectively.